FOXO1 is downregulated in obese mice subjected to short‐term strength training. Issue 11 (20th September 2022) - Pereira, Rodrigo M.; da Cruz Rodrigues, Kellen C.; Sant'Ana, Marcella R.; da Rocha, Alisson L.; Morelli, Ana P.; Veras, Allice S. C.; Gaspar, Rodrigo S.; da Costa Fernandes, Célio J.; Teixeira, Giovana R.; Simabuco, Fernando M.; da Silva, Adelino S. R.; Cintra, Dennys E.; et al.
Abstract: Obesity is a worldwide health problem and is directly associated with insulin resistance and type 2 diabetes. The liver is an important organ for the control of healthy glycemic levels, since insulin resistance in this organ reduces phosphorylation of forkhead box protein 1 (FOXO1) protein, leading to higher hepatic glucose production (HGP) and fasting hyperglycemia. Aerobic physical training is known as an important strategy in increasing the insulin action in the liver by increasing FOXO1 phosphorylation and reducing gluconeogenesis. However, little is known about the effects of strength training in this context. This study aimed to investigate the effects of short‐term strength training on hepatic insulin sensitivity and glycogen synthase kinase‐3β (GSK3β) and FOXO1 phosphorylation in obese (OB) mice. To achieve this goal, OB Swiss mice performed the strength training protocol (one daily session for 15 days). Short‐term strength training increased the phosphorylation of protein kinase B and GSK3β in the liver after insulin stimulus and improved the control of HGP during the pyruvate tolerance test. On the other hand, sedentary OB animals reduced FOXO1 phosphorylation and increased the levels of nuclear FOXO1 in the liver, increasing the phosphoenolpyruvate carboxykinase (PEPCK) and glucose‐6‐phosphatase (G6Pase) content. The bioinformatics analysis also showed positive correlations between hepatic FOXO1 levels and gluconeogenic genes, reinforcing our findings. However, strength‐trained animals reverted to this scenario, regardless of body adiposity changes. In conclusion, short‐term strength training is an efficient strategy to enhance the insulin action in the liver of OB mice, contributing to glycemic control by reducing the activity of hepatic FOXO1 and lowering PEPCK and G6Pase contents.